Effects of organisational ambidexterity and change for sustainability on organisational effectiveness: empirical evidence from India. (2014) - Vihari, Nitin Simha; Rao, M.K.
The increasing interest in both practice and scholarship is facilitating the ongoing research on corporate sustainability. The aim of this paper is to investigate the influence of organisational ambexterity (OA) and organisational change for sustainability (OCS) in achieving corporate sustainability (CS) and in turn contributing to the organisational effectiveness. In addition to the above mentioned direct relationships, the study further explores the interaction effects of the moderating variables such as employee integration (EI) and resource endowments (RE). The study is undertaken in the context of select pharmaceutical companies in India with a sample size of 245 respondents. Structural equation modelling was used as a method for the statistical validation of the latent constructs. The key finding of the study reveals that OA, OCS significantly predicts and also explains the variability of the latent constructs CS and OE.